DEVELOPMENT OF GEL COMPOSED INHIBITOR AGAINST CHLORIDE ATTACK IN A TRANSMISSION LINE SHIELD TUNNEL - SHINOGUCHI, Saeko; WATANABE, Tomomi; MIYAZATO, Shinichi; OKA, Shigeaki (Cement Science and Concrete Technology, 2025)
It is concerned that salt damage due to water leakage happens at a RC shield transmission tunnel nearby bay area. To prevent this corrosion, gel composed inhibitor have been developed. By this gel, corrosion inhibitor permeates through the concrete surface and guard reinforcement against chloride attack. This gel, however, is optimized for conventional concrete whose W/C is around 55％. In this study, we developed gel composed inhibitor, which is capable of penetrating corrosion inhibitors into concrete whose W/C is lower such as 35％.